Model Theory and Applications - Mangani, P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Lectures: G.E. Sacks: Model theory and applications.- H.J. Keisler: Constructions in model theory.- Seminars: M. Servi: SH formulas and generalized exponential.- J.A. Makowski: Topological model theory.
Lectures: G.E. Sacks: Model theory and applications -- H.J. Keisler: Constructions in model theory -- Seminars: M. Servi: SH formulas and generalized exponential -- J.A. Makowski: Topological model theory.
Keywords: Mathematics; Logic, Symbolic and mathematical; Mathematics; Mathematical Logic and Foundations